KEDUDUKAN KEBIJAKAN PEMERINTAH KOTA SURABAYA UNTUK TIDAK MEMBERIKAN PELAYANAN PUBLIK KEPADA SUAMI YANG DIPUTUS BERCERAI OLEH PENGADILAN AGAMA SEBELUM KEWAJIBAN NAFKAH DIPENUHI - Franklin, Yohanes; Sesung, Rusdianto (Fakultas Hukum Universitas Narotama, 2025)
Licensing is one form of administrative public service provided by the government to the community. To ensure the fulfillment of rights and legal certainty for the community in obtaining licensing services, the government, especially the regional government, has prepared service standards which are stated in the form of a Regional Head Decree or a Regional Apparatus Head Decree. However, the right to obtain licensing services can be limited if there is a court decision that has permanent legal force ordering the regional government not to provide licensing services to a person or legal entity. In order to protect the rights of women and children after divorce, the Surabaya City Government and the Surabaya City Religious Court have made an agreement containing a policy not to provide public services including licensing services to husbands who have not fulfilled their obligation to provide support based on a court decision issued by the Surabaya City Religious Court. The legal issue of concern is the validity of the contents of the Surabaya City Religious Court Decision considering that divorce cases are cases of the parties and the regional government is not a party to the case. Based on general legal principles, judges in deciding cases are prohibited from taking legal action without legal authority. In this case, the divorce dispute filed by the parties only discusses the resolution of the dispute that occurs between the parties. With the existence of the Surabaya City Religious Court Decision which has permanent legal force, the Surabaya City Government is bound not to provide licensing services. Keywords: Licensing Services; Regional Government Policy; Protection of Women and Children